2017
DOI: 10.3389/fpubh.2017.00064
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Population Vulnerability to Heat Wave in Western Australia

Abstract: Heat waves (HWs) have killed more people in Australia than all other natural hazards combined. Climate change is expected to increase the frequency, duration, and intensity of HWs and leads to a doubling of heat-related deaths over the next 40 years. Despite being a significant public health issue, HWs do not attract the same level of attention from researchers, policy makers, and emergency management agencies compared to other natural hazards. The purpose of the study was to identify risk factors that might l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 33 publications
1
60
2
2
Order By: Relevance
“…In this context, the Australian Bureau of Meteorology (BOM) recently introduced a map-based heatwave forecasting service using the Excess Heat Factor (EHF) metric based on average daily temperatures (Nairn and Fawcett 2014). Recent studies that have used the EHF as an exposure metric in the assessment of health impacts have found it to be a useful heatwave indicator (Hatvani-Kovacs et al 2016;Jegasothy et al 2017;Scalley et al 2015;Williams et al 2018;Xiao et al 2017). The EHF is also becoming widely used internationally due to its applicability in both tropical and temperate regions, and as such is included in the World Health Organization (WHO) and World Meteorological Organization (WMO) guidance documents on warning systems (World Meterological Organization and World Health Organization 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the Australian Bureau of Meteorology (BOM) recently introduced a map-based heatwave forecasting service using the Excess Heat Factor (EHF) metric based on average daily temperatures (Nairn and Fawcett 2014). Recent studies that have used the EHF as an exposure metric in the assessment of health impacts have found it to be a useful heatwave indicator (Hatvani-Kovacs et al 2016;Jegasothy et al 2017;Scalley et al 2015;Williams et al 2018;Xiao et al 2017). The EHF is also becoming widely used internationally due to its applicability in both tropical and temperate regions, and as such is included in the World Health Organization (WHO) and World Meteorological Organization (WMO) guidance documents on warning systems (World Meterological Organization and World Health Organization 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with the fact that the UHI is a typically nighttime phenomenon [53,57] when the radiation stored during the day in the densely built-up areas is released into the atmosphere during the night [29]. These findings are especially useful in a country such as Italy where frequent and often intense heat waves occur during summer, and a general increased earliness in the occurrence of the most critical heat waves was observed at the end of June [58], when day-length is a risk factor with often devastating effects for the general population and especially the most vulnerable subjects [59,60].…”
mentioning
confidence: 99%
“…Big data is a component in studies that have shown new precision characteristics of such public health concerns as cholera ( 141 ), chikungunya ( 142 ), diabetes ( 143 , 144 ), diarrhea ( 145 ), heatwave ( 146 ), influenza ( 147 ), opioid epidemic ( 148 , 149 ), preterm birth ( 150 ), stunting ( 151 ), and Zika ( 152 ).…”
Section: Understanding Diseasementioning
confidence: 99%